Feathers and food: Human-bird interactions at Middle Pleistocene Qesem Cave, Israel. Issue 136 (November 2019) - Blasco, Ruth; Rosell, Jordi; Sánchez-Marco, Antonio; Gopher, Avi; Barkai, Ran
Abstract: The presence of fast-moving small game in the Paleolithic archaeological faunal record has long been considered a key variable to assess fundamental aspects of human behavior and subsistence. Birds occupy a prominent place in this debate not only due to their small size and to the difficulties in capturing them (essentially due to their ability to fly and their elusiveness), but also due to their possible role in the symbolic array in regard to non-nutritional elements (feathers, talons, etc.) and as reflectors of complex human–world relationships. In this study, we attempt to contribute to this topic by presenting taphonomical data of bird specimens from Qesem Cave (Israel), dated between 420 and 200 ka. Human-induced damage, including cut marks, peeling and human gnawing, has been identified on wing bones of Cygnus sp., Columba sp., Corvus ruficollis and Sturnus sp. Our evidence suggests that avian exploitation was not limited to food only—either to complement the human diet or as occasional food item—but also presumably for the use of feathers. While the consumption of birds as a dietary source seems to be evident as early as the Early Pleistocene, the non-alimentary use of inedible elements, such as feathers and talons, appears to be a practice from the Middle Paleolithic onwards. We argue that the combined nutritional and symbolic use of birds is one characteristic of the new mode of adaptation practiced already by the late Lower Paleolithic Acheulo-Yabrudian hominins in the Levant starting 400 ka. The Qesem findings point to the possible emergence of new cognitive and behavioral skills, which are followed in later periods in the Old World. Finally, we discuss the possible ontological and cosmological significance of human–bird interactions to illuminate our hypothesis regarding the emergence of a new perception of human relationships with the world as an integral part of the new Acheulo-Yabrudian mode of adaptation.